EFEKTIFITAS SALEP MINYAK BUAH MERAH TERHADAP PROSES PENYEMBUHAN LUKA SAYATAN PADA TIKUS GALUR WISTAR LUKA DIABETIK STADIUM II - Daud Yusuf Rumbrawer; Ari Suwando; Arwani Arwani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
Wound retinopathy until now is the main health problems of around the world, especially in indonesia because the case with the increasing, wound is chronic and difficult recover, a sinus infection and ischemia a limb with the risk amputation even life-threatening.Oil red fruit containing various active component namely α- karoten, β-karoten, β-kriptosantin and α-tokoferol, and fatty acids not saturated, especially oleic acid, linoleic and palmitoleat who efficacious treat eyes shortsighted, itching, wound scratched, sore and tired, drains hair, treat cancer and degenerative diseases (the heart, cholesterol, diabetes, high blood).The study is done to prove the effectiveness of an ointment oil fruit red (pandanus conoideus oil) of the healing process wound incision in mouse galur wistar (rattus novergicus) wound retinopathy stage two. This type of research is True Experimental Design, the research design pretest - posttest control group design. Subject of research that 27 male wistar strain rats were divided into three groups: control (gauze NaCl 0.9%), the treatment group one ointment oil fruit red 15%, group twoointment oil fruit red 30%, respectively wistar strain rats were then given a drug injection adapted aloxan 125gr / kg /weight, to shut down its insulin and dilakuakan incisions (cuts) on the back 2 cm, control (gauze NaCl 0.9%), in love moist gauze every day, group one ointment red fruit 15%, and the group treatment of red fruit II ointment 30%, dioleska on the wound as well as closed and dilakuakan observations and measurements for 21 days to prove the diabetic wound healing process in the three groups. The results of statristik test control gauze Nacl 0.9 % and the treatment group two ointment oil fruit red 30% effective in day to 7, 14 and 21 test Post Hoc Tukey HSD obtained value p 0,032, experienced healing.While the control gauze Nacl 0.9 % and the treatment group one ointment oil fruit red 15% obtained value p 0,935 on the day 7th and on the day to the 14th and 21 effective, obtained value p 0,000. Conclusions: Red fruit oil lubrication 30% for 7 days to prove effective against the incision wound healing in rats wistar strain stage twodiabetic wounds significantly.